Yeast Metabolic Response as an Indicator of Radiation Damage in Biological Tissue. Issue 9 (8th August 2018) - Yoon, Chang Keun; Ochoa, Manuel; Kim, Albert; Rahimi, Rahim; Zhou, Jiawei; Ziaie, Babak
Abstract: Wearable radiation sensors for workers of radiation‐intensive industries provide a measure of radiation exposure but not of its effects on biological tissue. A biohybrid radiation sensing platform based on a new transduction mechanism for detecting biological radiation damage using the metabolic activity of a microorganism population is presented here. The sensor is a wearable, disposable, film‐type device fabricated on a paper substrate with yeast ( Saccharomyces cerevisiae ) cells patterned between two electrodes and used as a smart material. The device is sensitive to radiation when dry and is read by activating it with water. Yeast ( S. cerevisiae ) cells, that are exposed to ionizing radiation and subsequently allowed to ferment a glucose solution, exhibit an electrical conductivity that is lower than that of nonexposed yeast. The radiation damage to this microorganism is directly proportional to the measured impedance of the fermenting medium. An 18 × 18 mm 2 and 0.57 mm thick sensors with ground yeast (3.09 mg cm −2 areal density filtered with a 50 µm mesh) shows a sensitivity of 4.5% Ω/Ω0 decade‐rad upon exposure to Cs‐137. The minimum detectable dose (resolution) is 1 mrad. Fluorescence microscopy results suggest that it is primarily due to damaged membranes in the cell wall and mitochondria. Abstract : A wearable, disposable, film‐type radiation sensor is fabricated on a paper substrate with yeast ( S. cerevisiae ) cells that are patterned between two conductive electrodes. This smart biohybrid device detects biological radiation damage using the metabolic activity of a microorganism population with a sensitivity of 4.5% Ω/Ω0 decade‐rad upon exposure to Cs‐137 and a minimum detectable dose (resolution) of 1 mrad.